Assessing the potential to scale-up urban agriculture in the Global North - Jason K. Hawes; Dimitrios Gounaridis; Joshua P. Newell; Benjamin P. Goldstein; Silvio Caputo; Nevin Cohen; Agnès Fargue-Lelièvre; Lidia Poniży; Kathrin Specht (Landscape and Urban Planning, 2026)

Stock composition and movement patterns of striped bass in the Saco River Estuary, Maine, USA, using acoustic telemetry - Benjamin P. Gowell; Alexa Cacacie; Jessica B. Maguire; Ashley M. Nicoll; Mike G. Frisk; Keith J. Dunton; Craig Tennenhouse; Jason Doll; John A. Mohan; William Kochtitzky; Michelle Caputo (Estuarine, Coastal and Shelf Science, 2026)

The impacts of food chains: are alternative food networks sustainable? - S. Falasco; G. Ferla; P. Caputo; B. Mura; B. Borrello; M. Marson; V. León Bravo; F. Caniato (Clean Technologies and Environmental Policy, 2025)
The environmental impacts related to food production are of growing concern, with the phases of production and distribution that significantly contribute to greenhouse gas emissions. Among the call for sustainable food supply chains, Alternative Food Networks (AFNs) have emerged as alternatives to Large-Scale Retail (LSR), striving to promote a more sustainable food system. Research related to AFNs has primarily delved into the importance of local food, connection between producers and consumers or reduce the number of intermediaries. Even if AFNs are widely assumed to be more environmentally sustainable, there is a significant dearth of research on assessing their actual environmental performances. This paper aims to address this aspect of sustainability by analyzing the environmental impacts of AFNs, comparing them to the conventional model of food distribution (LSR), focusing on energy demand and climate change emissions. The study models four scenarios involving the distribution of oranges and carrots, supported by primary data, collected with an extensive interview with one manager for the AFN, and secondary data LSR. Results show that while AFNs perform better than LSR in the upstream logistics, the downstream perform worse, due to less efficient consumer travel patterns. Furthermore, the study evaluates an optimization scenario, revealing that modifying consumers means of transportation could significantly improve AFN performance. In conclusion, the results show how the environmental sustainability of AFNs should not be taken for granted, and how relevant last-mile logistics is for overall environmental sustainability of AFN. The study also provides useful insights for policy development and strategic initiatives aimed at enhancing sustainability and decarbonization in the food sector. Graphical abstract

Involving citizen scientists in monitoring arthropod vectors of human and zoonotic diseases: The case of Mosquito Alert in Italy - C. Virgillito; E. Longo; C.M. De Marco; P. Serini; M.V. Zucchelli; F. Montarsi; F. Severini; R. Rosà; D. Da Re; F. Filipponi; M. Manica; J. Palmer; et al. (Science of The Total Environment, 2024)

A Survival Analysis of Family Forest Owners in the USA: Estimating Life Expectancy and 5-Year Survivorship - Jesse Caputo; B. J. Butler; M. Markowski-Lindsay; P. Catanzaro (Small-scale Forestry, 2023)

Investigation of the Role of Hydrophobic Amino Acids on the Structure–Activity Relationship in the Antimicrobial Venom Peptide Ponericin L1 - Nicholas P. Schifano; Gregory A. Caputo (The Journal of Membrane Biology, 2022)

Seismic hazard for the Trans Adriatic Pipeline (TAP). Part 2: broadband scenarios at the Fier Compressor Station (Albania) - L. Moratto; A. Vuan; A. Saraò; D. Slejko; C. Papazachos; R. Caputo; D. Civile; V. Volpi; S. Ceramicola; A. Chatzipetros; S. Daja; P. Fabris; et al. (Bulletin of Earthquake Engineering, 2021)
To ensure environmental and public safety, critical facilities require rigorous seismic hazard analysis to define seismic input for their design. We consider the case of the Trans Adriatic Pipeline (TAP), which is a pipeline that transports natural gas from the Caspian Sea to southern Italy, crossing active faults and areas characterized by high seismicity levels. For this pipeline, we develop a Probabilistic Seismic Hazard Assessment (PSHA) for the broader area, and, for the selected critical sites, we perform deterministic seismic hazard assessment (DSHA), by calculating shaking scenarios that account for the physics of the source, propagation, and site effects. This paper presents a DSHA for a compressor station located at Fier, along the Albanian coastal region. Considering the location of the most hazardous faults in the study site, revealed by the PSHA disaggregation, we model the ground motion for two different scenarios to simulate the worst-case scenario for this compressor station. We compute broadband waveforms for receivers on soft soils by applying specific transfer functions estimated from the available geotechnical data for the Fier area. The simulations reproduce the variability observed in the ground motion recorded in the near-earthquake source. The vertical ground motion is strong for receivers placed above the rupture areas and should not be ignored in seismic designs; furthermore, our vertical simulations reproduce the displacement and the static offset of the ground motion highlighted in recent studies. This observation confirms the importance of the DSHA analysis in defining the expected pipeline damage functions and permanent soil deformations.

Seismic hazard for the Trans Adriatic Pipeline (TAP). Part 1: probabilistic seismic hazard analysis along the pipeline - D. Slejko; A. Rebez; M. Santulin; J. Garcia-Pelaez; D. Sandron; A. Tamaro; D. Civile; V. Volpi; R. Caputo; S. Ceramicola; A. Chatzipetros; S. Daja; et al. (Bulletin of Earthquake Engineering, 2021)
The design of critical facilities needs a targeted computation of the expected ground motion levels. The Trans Adriatic Pipeline (TAP) is the pipeline that transports natural gas from the Greek-Turkish border, through Greece and Albania, to Italy. We present here the probabilistic seismic hazard analysis (PSHA) that we performed for this facility, and the deaggregation of the results, aiming to identify the dominant seismic sources for a selected site along the Albanian coast, where one of the two main compressor stations is located. PSHA is based on an articulated logic tree of twenty branches, consisting of two models for source, seismicity, estimation of the maximum magnitude, and ground motion. The area with the highest hazard occurs along the Adriatic coast of Albania (PGA between 0.8 and 0.9 g on rock for a return period of 2475 years), while strong ground motions are also expected to the north of Thessaloniki, Kavala, in the southern Alexandroupolis area, as well as at the border between Greece and Turkey. The earthquakes contributing most to the hazard of the test site at high and low frequencies (1 and 5 Hz) and the corresponding design events for the TAP infrastructure have been identified as local quakes with M W 6.6 and 6.0, respectively.

Use of radiofrequency electromagnetic radiation to remove biofilms from canvasses - P. Cennamo; N. Pasquino; C. Ciniglia; A. Moretti; P. Caputo (Aerobiologia, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Letter to the editor: switching treatment to lamivudine plus boosted atazanavir or darunavir in virologically suppressed HIV-infected patients – evidence from a large observational cohort - D. F. Bavaro; D. Di Carlo; P. Zuccalà; F. Bai; F. Incardona; A. Battisti; S. Giachè; E. Salomoni; R. Gagliardini; S. Di Giambenedetto; M. Pecorari; M. Zazzi; et al. (Infectious Diseases, 2019)

Brown trout (Salmo trutta L.) high genetic diversity around the Tyrrhenian Sea as revealed by nuclear and mitochondrial markers - P. Berrebi; V. Caputo Barucchi; A. Splendiani; S. Muracciole; A. Sabatini; F. Palmas; C. Tougard; M. Arculeo; S. Marić (Hydrobiologia, 2019)

Reinventing rice husk ash: derived NaX zeolite as a high-performing CO2 adsorbent - N. Gargiulo; K. Shibata; A. Peluso; P. Aprea; T. Valente; G. Pezzotti; T. Shiono; D. Caputo (International Journal of Environmental Science and Technology, 2018)

Population genetics analysis in a relic population of silver fir ( Abies alba Mill.) in southern Italy: A comparison with microsatellites and reference data - D. De Luca; B. Menale; P. Caputo; P. Cennamo (Plant Biosystems, 2017)

Museum samples could help to reconstruct the original distribution of Salmo trutta complex in Italy - A. Splendiani; T. Fioravanti; M. Giovannotti; L. Olivieri; P. Ruggeri; P. Nisi Cerioni; S. Vanni; F. Enrichetti; V. Caputo Barucchi (Journal of Fish Biology, 2017)
Partial D‐loop sequences of museum specimens of brown trout and marble trout ( Salmo trutta species complex ) collected from Mediterranean rivers in the late 19th century were analysed to help to describe the native distribution of these species. All the individuals studied carried native haplotypes, the geographic distribution of which is consistent with published data. These results indicate that museum specimens from the 19th century could represent an opportunity to get a picture of the original genetic diversity distribution of this species complex.

Asperula calabra (Rubiaceae) and allied taxa in southern Apennines, Italy - E. Del Guacchio; R. Gargiulo; P. Caputo (Plant Biosystems, 2017)

Diversity of phototrophic components in biofilms from Piperno historical stoneworks - P. Cennamo; P. Caputo; C. Marzano; A. Z. Miller; C. Saiz-Jimenez; A. Moretti (Plant Biosystems, 2016)

Alien brown trout invasion of the Italian peninsula: the role of geological, climate and anthropogenic factors - A. Splendiani; P. Ruggeri; M. Giovannotti; S. Pesaresi; G. Occhipinti; T. Fioravanti; M. Lorenzoni; P. Nisi Cerioni; V. Caputo Barucchi (Biological Invasions, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Prominent intraspecific genetic divergence within Anopheles gambiae sibling species triggered by habitat discontinuities across a riverine landscape - B. Caputo; D. Nwakanma; F. P. Caputo; M. Jawara; E. C. Oriero; M. Hamid‐Adiamoh; I. Dia; L. Konate; V. Petrarca; J. Pinto; D. J. Conway; A. Della Torre (Molecular Ecology, 2014)
The Anopheles gambiae complex of mosquitoes includes malaria vectors at different stages of speciation, whose study enables a better understanding of how adaptation to divergent environmental conditions leads to evolution of reproductive isolation. We investigated the population genetic structure of closely related sympatric taxa that have recently been proposed as separate species ( An. coluzzii and An. gambiae ), sampled from diverse habitats along the Gambia river in West Africa. We characterized putatively neutral microsatellite loci as well as chromosomal inversion polymorphisms known to be associated with ecological adaptation. The results revealed strong ecologically associated population subdivisions within both species. Microsatellite loci on chromosome‐3L revealed clear differentiation between coastal and inland populations, which in An. coluzzii is reinforced by a unusual inversion polymorphism pattern, supporting the hypothesis of genetic divergence driven by adaptation to the coastal habitat. A strong reduction of gene flow was observed between An. gambiae populations west and east of an extensively rice‐cultivated region apparently colonized exclusively by An. coluzzii . Notably, this ‘intraspecific’ differentiation is higher than that observed between the two species and involves also the centromeric region of chromosome‐X which has previously been considered a marker of speciation within this complex, possibly suggesting that the two populations may be at an advanced stage of differentiation triggered by human‐made habitat fragmentation. These results confirm ongoing ecological speciation within these most important Afro‐tropical malaria vectors and raise new questions on the possible effect of this process in malaria transmission.

Karyological and molecular characterisation of subgenus Vicia (Fabaceae) - P. Caputo; M. Frediani; M. T. Gelati; G. Venora; R. Cremonini; M. Ruffini Castiglione (Plant Biosystems, 2013)

Isolation and characterisation of novel microsatellite loci in the transparent goby Aphia minuta (Perciformes, Gobiidae) - P. Ruggeri; A. Splendiani; M. Giovannotti; T. Fioravanti; P. Nisi Cerioni; V. Caputo (Conservation Genetics Resources, 2013)

Isolation of novel microsatellite loci in the black goby Gobius niger and cross‐amplification in other gobiid species (Perciformes, Gobiidae) - P. Ruggeri; A. Splendiani; M. Giovannotti; P. Nisi Cerioni; V. Caputo (Journal of Fish Biology, 2012)
Twelve microsatellite loci were isolated from and characterized for the black goby Gobius niger . These loci were tested on a total of 48 individuals from two geographically distant locations (Orbetello and Cattolica) and the number of alleles ranged from two to 18, with expected ( H e ) and observed ( H o ) heterozygosities ranging from 0·042 to 0·941 and from 0·042 to 0·917, respectively. The loci described were used to cross‐amplify other gobiid species belonging to Gobius , Zosterisessor , Lesueurigobius and Aphia .

Cytological and molecular characterization of Vicia barbazitae Ten. & Guss. - M. Ruffini Castiglione; M. Frediani; M. T. Gelati; G. Venora; L. Giorgetti; P. Caputo; R. Cremonini (Protoplasma, 2012)

Identification of a new susceptibility variant for multiple sclerosis in OAS1 by population genetics analysis - Rachele Cagliani; Matteo Fumagalli; Franca R. Guerini; Stefania Riva; Daniela Galimberti; Giacomo P. Comi; Cristina Agliardi; Elio Scarpini; Uberto Pozzoli; Diego Forni; Domenico Caputo; Rosanna Asselta; et al. (Human Genetics, 2012)

Cytology of Vicia species. X. Karyotype evolution and phylogenetic implication in Vicia species of the sections Atossa, Microcarinae, Wiggersia and Vicia - M. Ruffini Castiglione; M. Frediani; M. T. Gelati; C. Ravalli; G. Venora; P. Caputo; R. Cremonini (Protoplasma, 2011)

Chromosomal evolution in Gekkonidae. I. Chromosome painting between Gekko and Hemidactylus species reveals phylogenetic relationships within the group - Vladimir A. Trifonov; Massimo Giovannotti; Patricia C. M. O’Brien; Margaret Wallduck; Frances Lovell; Willem Rens; Patricia P. Parise-Maltempi; Vincenzo Caputo; Malcolm A. Ferguson-Smith (Chromosome Research, 2011)

Molecular markers in Viola L. subsect. Viola : Application and taxonomic implications for the identification of dubious herbarium specimens - P. Cennamo; E Del Guacchio; S. L. Jury; P. Caputo (Plant Biosystems, 2011)

Mitochondrial DNA variation of an isolated population of the Adriatic brook lamprey Lampetra zanandreai (Agnatha: Petromyzontidae): phylogeographic and phylogenetic inferences - V. Caputo; M. Giovannotti; P. Nisi Cerioni; A. Splendiani; M. Marconi; J. Tagliavini (Journal of Fish Biology, 2009)
Two mitochondrial genes were examined to compare an isolated population of the Adriatic brook lamprey Lampetra zanandreai in central Italy with other populations in the species range (Po plain) and with parasitic and freshwater lampreys. A single haplotype, identical to one in a Venetian sample, was found in 10 individuals from the isolated population. The reduced variability is consistent with a history of dispersal after the Pleistocene expansion of the Po basin. The results support the hypothesis of an origin of L. zanandreai and L. fluviatilis – L. planeri from a common anadromous ancestor.

A phylogenetic analysis of Dipsacaceae based on four DNA regions - M. Avino; G. Tortoriello; P. Caputo (Plant Systematics and Evolution, 2009)

Cytological and molecular characterization of Vicia esdraelonensis Warb. & Eig: a rare taxon - M. Ruffini Castiglione; M. Frediani; M. T. Gelati; C. Ravalli; G. Venora; P. Caputo; R. Cremonini (Protoplasma, 2007)

Depolymerisation and rearrangement of actin filaments during exocytosis in rat peritoneal mast cells: involvement of ryanodine-sensitive calcium stores - R. E. Guzmán; P. Bolaños; A. Delgado; H. Rojas; R. DiPolo; C. Caputo; E. H. Jaffe (Pflügers Archiv - European Journal of Physiology, 2007)

Nuclear DNA contents, rDNAs, and karyotype evolution in subgenus Vicia: III. The heterogeneous section Hypechusa - P. Caputo; M. Frediani; G. Venora; C. Ravalli; M. Ambrosio; R. Cremonini (Protoplasma, 2006)

Nuclear DNA contents, rDNAs, and karyotype evolution in Vicia subgenus Vicia: II. Section Peregrinae - M. Frediani; P. Caputo; G. Venora; C. Ravalli; M. Ambrosio; R. Cremonini (Protoplasma, 2005)

Genetic diversity of brown trout in central Italy - V. Caputo; M. Giovannotti; P. Nisi Cerioni; M. L. Caniglia; A. Splendiani (Journal of Fish Biology, 2004)
Genetic diversity was analysed in brown trout Salmo trutta populations living in an area of central Italy using RFLP analysis of two mtDNA segments and of the nuclear locus LDH‐C1 *. The data indicated a genetic structure profoundly altered by repeated stockings with allochthonous material of Atlantic origin. In fact, four and 11 of the haplotypes detected were, respectively, identical or genetically very close to haplotypes found in Danish populations, the putative source of stocked brown trout. Furthermore, the LDH‐C1 * 90 allele, typical of north‐western Europe, was widespread among the samples studied. Nonetheless, four populations are characterized by a high frequency of both putative autochthonous haplotypes and the LDH‐C1 * 100 allele, common in the Mediterranean basin. These populations, sampled in areas where S. trutta is documented historically, might represent a remnant of the species’ indigenous biodiversity, showing the scope for improving the management of brown trout in central Italy.

Molecular phylogenetics of Dipsacaceae reveals parallel trends in seed dispersal syndromes - P. Caputo; S. Cozzolino; A. Moretti (Plant Systematics and Evolution, 2004)

The reproductive biology of the crystal goby with a comparison to that of the transparent goby - V. Caputo; M. L. Mesa; G. Candi; P. N. Cerioni (Journal of Fish Biology, 2003)
A histological analysis of the gonad of the pelagic crystal goby Crystallogobius linearis , from the coastal central area of the Adriatic Sea, showed it to be a truly semelparous species; after the first spawning the mature gonads of both males and females appeared to have lost the capability for further spawning. Mature females had very low fecundity (200–700 mature oocytes) and small egg size (0·2–0·55 mm) similarly to other progenetic species. This reproductive strategy is compared with that of Aphia minuta , and a possible cause for the post‐reproductive mortality of the two gobies is suggested and discussed.

Molecular relationships in Genista L. Sect. Spartocarpus Spach (Fabaceae) - O. De Castro; S. Cozzolino; S. L. Jury; P. Caputo (Plant Systematics and Evolution, 2002)

Short lifespan and apoptosis in Aphia minuta - V. Caputo; G. Candi; E. Arneri; M. La Mesa; C. Cinti; M. Provinciali; P. Nisi Cerioni; A. Gregorini (Journal of Fish Biology, 2002)
Evidence is presented that apoptosis of intestinal enterocytes is implicated in adult mortality immediately after the breeding season in Aphia minuta , a paedomorphic goby that spends its whole life cycle of

Cytogenetics of nine species of Mediterranean blennies and additional evidence for an unusual multiple sex-chromosome system in Parablennius tentacularis (Perciformes, Blenniidae) - V. Caputo; N. Machella; P. Nisi-Cerioni; E. Olmo (Chromosome Research, 2001)

Patterns of relationships inTrichostomoideae (Pottiaceae, Musci) - V. Spagnuolo; P. Caputo; S. Cozzolino; R. Castaldo; P. De Luca (Plant Systematics and Evolution, 1999)

Opposite effects of cooling on twitch contractions of skeletal muscle isolated from tropical toads (Leptodactylidae) and northern frogs (Ranidae) - C. Caputo; C. Gerday; J. R. Lopez; S. R. Taylor; P. Bolaños (Journal of Comparative Physiology B, 1998)

Aquifer-induced Seismicity in the Central Apennines (Italy) - F. Bella; P. F. Biagi; M. Caputo; E. Cozzi; G. Della Monica; A. Ermini; W. Plastino; V. Sgrigna (Pure and Applied Geophysics, 1998)

Characterization of Orchis x dietrichiana Bogenh., a natural orchid hybrid - S. COZZOLINO; S. ACETO; P. CAPUTO; B. MENALE (Plant Biosystems, 1998)

Morphological and molecular characterization of a natural hybrid betweenOrchis laxiflora andO. morio (Orchidaceae) - P. Caputo; S. Aceto; S. Cozzolino; R. Nazzaro (Plant Systematics and Evolution, 1997)

New BK virus episomal vector for complementary DNA expression in human cells - M. P. Grossi; A. Caputo; P. Rimessi; L. Chiccoli; P. G. Balboni; G. Barbanti-Brodano (Archives of Virology, 1988)

Factors affecting amplification of BK virus episomal vectors in human cells - M. P. Grossi; A. Caputo; L. Paolini; P. G. Balboni; G. Gerna; M. Pagnani; A. Corallini; G. Barbanti-Brodano (Archives of Virology, 1988)

Oncogenity of BK virus for immunosuppressed hamsters - A. Corallini; G. Altavilla; L. Carra; M. P. Grossi; G. Federspil; A. Caputo; M. Negrini; G. Barbanti-Brodano (Archives of Virology, 1982)